Are colored periodontal probes reliable to classify the gingival phenotype in terms of gingival thickness?. Issue 3 (13th September 2021) - Bertl, Kristina; Al‐Hotheiry, Mehdi; Sun, David; Olofsson, John; Lettner, Stefan; Gotfredsen, Klaus; Stavropoulos, Andreas
Abstract: Background: This cross‐sectional study assessed the potential of colored periodontal probes (CPP) to classify gingival phenotype in terms of gingival thickness (GT). Methods: Buccal GT in three anterior teeth in each of 50 patients was measured by transgingival sounding and classified by three different methods by eight examiners. Specifically, the diagnostic potential of visual judgment and transparency of a standard periodontal probe (SPP) to discriminate thin and thick gingiva, and of CPP to discriminate thin, medium, thick, or very thick gingiva was assessed. Results: GT ranged from 0.57 to 2.37 mm. Using CPP resulted in a medium judgment in 87% of the cases, on average, and only between 1‐10 cases/examiner were judged as thick or very thick. Considering 1 mm GT as relevant cut‐off value, all methods showed a high positive predictive value (≥ 0.82) to identify thick cases, but also a high false omission rate (≥ 0.73) indicating that many cases classified as thin were actually thick. Further, 88% of the cases being ≤ 1 mm, were not classified as thin with CPP; this was inferior to SPP, for which, however, still 64% of the cases being ≤ 1 mm thick were wrongly classified. The highest, yet moderate agreement among examiners was achieved by SPP (κ = 0.427), whereas visual judgment and CPP showed only fair (κ = 0.211) and slight agreement (κ = 0.112), respectively. Conclusion: Using CPP resulted in most of the cases in a medium judgment. It seems that CPP cannot distinctly discriminate between "thick" and "very thick" cases and fails to capture the thin high‐risk cases.